Policy-Driven Network Traffic Rerouting Through Intent-Based Control Loops - Saraiva, Nathan; Islam, Nazrul; Lachos Perez, Danny Alex; Esteve Rothenberg, Christian (Anais do Workshop de Gerência e Operação de Redes e Serviços (WGRS), 2019)
Year after year, the growth of video traffic over the Internet keeps increasing. Video streaming over best-effort networks is considered inefficient and inappropriate to meet the expected Quality of Experience (QoE) of the new generation of multimedia services. Over the past few years, a number of technologies have emerged to improve the state of the art of video delivery, including HTTP Adaptive Streaming (HAS) that adapts the bitrate according to network conditions. At the crossroads, Software Defined Networking (SDN) offers options to meet Quality of Service (QoS) objectives for improved video quality by exploiting end-to-end programmability of network behaviour. However, traditional SDN approaches require dealing with low-level details from the underlying infrastructure, interfering in the automation and agility of service deployments. To alleviate these issues and overall provide a simpler approach, Intent-Based Networking (IBN) is being proposed to abstract low-level configurations through high-level policy interfaces. In this paper, we explore such an approach by implementing intent-based control loops for video service assurance. The proposed methods dynamically reconfigure the network for service-specific requirements using IBN to define the high-level behavior. We experimentally evaluate a use case where video traffic is rerouted based on network conditions to improve the QoS. The Proof-of-Concept results point to the potential of improving video content delivery through QoS-aware Intent-based approaches.